KAJIAN TENTANG PEMBAGIAN HARTA BERSAMA SEBAGAI AKIBAT TERJADINYA PERCERAIAN DI KABUPATEN BANTUL (Studi Kasus Putusan Pengadilan Agama Bantul Perkara Nomor : 0834/Pdt.G/2014/PA.Btl) - Sri Suwarni (Kajian Hukum, 2016)
The purpose of this study was to determine the legal basis of Judge in Bantul Religious Court consideration in providing case verdict division of joint property in Case No. 0834 / Pdt.G / 2014 / PA . Btl and also to investigate the implementation of the division of joint property as a result of divorce that have been in implemented in the Bantul Religious Court.This research was conducted by the method of research is also carried out literature research and field research. In the research literature studies document the means used to obtain secondary data, while the field research conducted to obtain primary data with qualitative approach with interviews. Data obtained from the research literature and field research analyzed qualitatively. The data is further described by the descriptive method of analysis, that in discussing the problems done by identifying, analyzing and interpreting the data that has been acquired to be concluded.Based on the results known that; Judge basic consideration in deciding the case division of the joint property polygamous marriages in Case No. 0834 / Pdt.G / 2014 / PA.Btl explicitly or implicitly in accordance with the legislation in force, namely the provisions of Article 35 of Law No. 1 of 1974 jo. Article 1 letter (f) Compilation of Islamic Law, the provisions of Article 94 Compilation of Islamic Law and the Decree of the Chairman of the Supreme Court of the Republic of Indonesia Number KMA / 032 / SK / IV / 2006, and the implementation of the division of joint property in Case No. 0834 / Pdt.G / 2014 / PA.Btl ultimately realized by deliberation / kinship between the parties and approved divided in accordance with a court decision, the joint property in a marriage that has not been divided by 3 and then divided equally, because the marriage the Plaintiff and Defendant I was polygamous marriages so that the Plaintiff 1/3 parts, Defendant I and Defendant II 2/3 and the realization of the division of joint property is evidently well received by the parties, so that between the parties feel that justice, and stay in touch in silahturami or good relations between them.